Asbestos base and asbestos free brake lining materials : comparative study - Shinde, Dinesh; Mistry, K.N. (International Journal of Scientific World, 2017)
Frictional brake lining materials are broadly made of asbestos as their constituent. But asbestos is dangerous for handling due to health hazardous. Asbestos has ample physical, mechanical and tribological properties. The material replacing it should have all these properties with no undermine. In this paper a study on asbestos base and asbestos free brake lining material is presented. Purpose behind this is combine the demerits of asbestos free and asbestos base materials with comparable properties. Some organic waste from farm like banana peel, palm karnel shell, were also tested for the replacement of asbestos and they found worth through comparison with each others.